Meta-analysis of hybrid natural-orifice transluminal endoscopic surgery versus laparoscopic surgery. Issue 8 (13th June 2017) - Steinemann, D C; Müller, P C; Probst, P; Schwarz, A-C; Büchler, M W; Müller-Stich, B P; Linke, G R
Abstract: Background: Hybrid natural-orifice transluminal endoscopic surgery (NOTES), combining access through a natural orifice with small-sized abdominal trocars, aims to reduce pain and enhance recovery. The objective of this systematic review and meta-analysis was to compare pain and morbidity in hybrid NOTES and standard laparoscopy. Methods: A systematic literature search was performed to identify RCTs and non- RCTs comparing hybrid NOTES and standard laparoscopy. The main outcome was pain on postoperative day (POD) 1. Secondary outcomes were pain during the further postsurgical course, rescue analgesia, complications, and satisfaction with the cosmetic result. The results of meta-analysis in a random-effects model were presented as odds ratio (ORs) or standard mean differences (MDs) with 95 per cent confidence intervals. Results: Six RCTs and 21 non-randomized trials including 2186 patients were identified. In hybrid NOTES the score on the numerical pain scale was lower on POD 1 (−0·75, 95 per cent c.i. −1·09 to −0·42; P = 0·001) and on POD 2–4 (−0·58, −0·91 to −0·26; P < 0·001) than that for standard laparoscopy. The need for rescue analgesia was reduced in hybrid NOTES (OR 0·36, 0·24 to 0·54; P < 0·001). The reduction in complications found for hybrid NOTES compared with standard laparoscopy (OR 0·52, 0·38 to 0·71; P < 0·001) was not significant when only RCTs were considered (OR 0·83, 0·43 to 1·60; P = 0·570). The score for cosmetic satisfaction was higher after NOTES (MD 1·14, 0·57 to 1·71; P < 0·001). Conclusion: Hybrid NOTES reduces postoperative pain and is associated with greater cosmetic satisfaction in selected patients. Abstract : Less pain was the only gain